Historical biogeography of the neotropical Diaptomidae (Crustacea: Copepoda) - Perbiche-Neves, Gilmar; Previattelli, Daniel; Pie, Marcio R.; Duran, Andressa; Suarez-Morales, Eduardo; Boxshall, Geoffrey A.; Nogueira, Marcos G. [UNESP]; Rocha, Carlos E. F. da (Biomed Central Ltd., 2014)
Introduction: Diaptomid copepods are prevalent throughout continental waters of the Neotropics, yet little is known about their biogeography. In this study we investigate the main biogeographical patterns among the neotropical freshwater diaptomid copepods using Parsimony Analysis of Endemicity (PAE) based on species records within ecoregions. In addition, we assess potential environmental correlates and limits for species richness.Results: PAE was efficient in identifying general areas of endemism. Moreover, only ecoregion area showed a significant correlation with diaptomid species richness, although climatic factors were shown to provide possible upper limits to the species richness in a given ecoregion.Conclusion: The main patterns of endemism in neotropical freshwater diaptomid copepods are highly congruent with other freshwater taxa, suggesting a strong historical signal in determining the distribution of the family in the Neotropics.
Keywords: America; Diaptominae; Diversity; Evolution; GIS; PAE; Richness